Awareness and Determinants of Telemedicine Adoption at Ga West District of Ghana - Hyde-Quartey, Linda; Hao, Chen; Adomako-Gyasi, Priscilla; Ahoto, Ahotovi Thomas (International Journal of Management Innovation Systems, 2024)
The need to have regular visitation to the hospital or be in the physical presence of healthcare professionals for treatment is gradually reducing. By the advancement in technology, an individual can receive treatment from the doctor or other health information through telemedicine. Telemedicine has gain ground in developed nations with many developing countries trying the adoption in practice. This study is a quantitative study that uses the question to collect data from respondents within the Ga West District in the Greater Accra Region of Ghana. A total of 226 respondents were involved in the study. The study aimed to measure the level of awareness about telemedicine among people living in the district, factors that influence the adoption of telemedicine and barriers preventing adoption. The findings indicated that there was a high level of awareness about telemedicine among the respondents with most of them knowing what telemedicine is. Adoption was also influenced by a reduction in treatment when use telemedicine, prevention of overcrowding at hospitals and the taken away of time wasted at the hospital. It was also determined that poor internet connectivity and high cost of data were the significant barriers impeding the adoption of telemedicine among the district dwellers.